Space-time and hadrons - Barros, Jr.,C. C. (2007)
The hadronic structure is investigated in terms of a recently proposed theory which considers the effect of the strong interaction in the space-time description. From the equations, the masses of the particles may be calculated, and quark confinement appears as a natural result, without the need of confining potentials. Some properties of the considered particles, such as the topponium size, are also estimated.